Renegotiating health care : resolving conflict to build collaboration - Marcus, Leonard J.; Dorn, Barry C.; McNulty, Eric J. (San Francisco : Jossey-Bass, 2011)
"This practical guide to negotiation and conflict resolution in the healthcare field, reveals why unresolved conflict can hamper any organization's ability to make timely decisions and implement new strategies. It focuses on the complex interactions between those that deliver, receive, administer, and oversee health care and outlines negotiation techniques and conflict resolution approaches that can positively impact efficiency, quality of care, and patient safety. This book should be required reading for students and professionals in health services management and administration, and conflict resolution professionals working in the health care field"--Provided by publisher.
Conflict -- Why conflict? -- Moving beyond conflict -- Setting the stage for negotiation -- Negotiation -- Interest-based negotiation -- Framing to generate options -- Reframing to spur momentum -- Walk in the woods -- Contest, resolution, and connectivity -- Positional bargaining -- Mediation, arbitration, and dispute resolution -- Meta-leadership -- Evolving health care practice -- Designing a more cohesive, better-linked health system -- Evolving with technology -- Negotiating patient -- Changing work and a changing workforce -- Shaping purpose -- Crafting the essentials -- Constructing a resilient balance.
Includes bibliographical references and index.
Keywords: Health planning -- Decision making; Conflict management; Negotiation; Medical policy -- Decision making; Medical care -- Decision making; Conflict management -- Decision making -- Case studies; Negotiation -- Case studies; Medical policy -- Decision making -- Case studies; Medical care -- Decision making -- Case studies; Health planning -- Decision making -- Case studies; Health Facility Administration; Conflict (Psychology); Interprofessional Relations; Negotiating; Professional-Patient Relations